DEBATED PROBLEMS OF PALEOCRYOLOGY OF THE PLEISTOCENE AND HOLOCENE OF WESTERN SIBERIA IN LIGHT OF NEW DATA - Vasilchuk Yu.K.; Trofimov V.T. (My University, 1984)
We have presented new data, connected with the use of oxygen isotope analysis. It was noted above that the age of epigenetic veins in the upper part of the cross section near the village of Seyakha are dated 9.3-8.7 thousand years ago. The content of delta180 in them was -19.4 to -20.3 promilles, i.e., 1-2 promilles isotopically lighter than modern; expressed as temperatures this difference can be estimated at 1-3°C lower than modern (we should also mention winter and early spring paleotemperatures). It is curious that the oxygen isotope composition of multiple vein ice in the series of first terrace near Kharasavei site, which probably formed in the "pre-optimal" period of the Holocene (according to a date 9560 ± 130 years BP (GIN-2650) from peat horizontally bedded over the head vein), turned out to be equal to 14-15.9 promilles, which is 2.5-4 promilles heavier than modern ice. This suggests temperatures of the winter and early spring period of the "pre-optimal" stage by at least 3-6°C exceeding modern. Unfortunately, we still do not have other reliably dated diagrams of the oxygen isotope composition of Holocene age. However, available material lets us make two essential conclusions. First, the oxygen isotope composition differs from modern and from the Holocene by its significantly lower content of stable oxygen isotopes, which agrees well with data-from oxygen isotope determinations of ice in Greenland and the Antarctic. Second, during the Holocene the oxygen isotope composition changed substantially; in some periods it was isotopically much lighter (at least at the beginning of the "optimum"), and in others heavier (in the "pre-optimal" stage 10-9 thousand years ago) than ice of modern syngenetic veins. Subsequent work will let us more exhaustively discuss this phenomenon and use it in solving problems of palaeocryology.
Keywords: ICE WEDGE; OXYGEN ISOROPE; PERMAFROST; HOLOCENE; LATE PLEISTOCENE; SIBERIA; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Quaternary::Holocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Голоцен